Dry needling — peripheral and central considerations - Dommerholt, Jan (Maney Publishing, 2011)
Dry needling is a common treatment technique in orthopedic manual physical therapy. Although various dry needling approaches exist, the more common and best supported approach targets myofascial trigger points. This article aims to place trigger point dry needling within the context of pain sciences. From a pain science perspective, trigger points are constant sources of peripheral nociceptive input leading to peripheral and central sensitization. Dry needling cannot only reverse some aspects of central sensitization, it reduces local and referred pain, improves range of motion and muscle activation pattern, and alters the chemical environment of trigger points. Trigger point dry needling should be based on a thorough understanding of the scientific background of trigger points, the differences and similarities between active and latent trigger points, motor adaptation, and central sensitize application. Several outcome studies are included, as well as comments on dry needling and acupuncture.